Contract Agreement for Consultancy Services Between Ministry of Agriculture and International Center for Agricultural Research in the Dry Areas; Up-scaling of community-based small ruminant breeding program in Ethiopia - Ministry of Agriculture, Ethiopia; International Center for Agricultural Research in the Dry Areas (Accelerating Impacts of CGIAR Climate Research for Africa, 2019)
MoU-Consultancy Services Between Ministry of Agriculture and International Center for Agricultural Research in the Dry Areas